Wintering Areas of the White-Tailed Eagle in Southern Kazakhstan - Elena S. Chalikova (Пернатые хищники и их охрана)
The White-Tailed Eagle (Haliaeetus albicilla) is a rare species with declining numbers listed in the Red Book of Kazakhstan. In the Turkestan Region it is present during migration and wintering periods with the earliest sighting on September 10 (2018), and the latest on March 23 (2021) (Koksarai Reservoir, Gubin, 2020). Since 2003, wintering birds have been regularly observed on water bodies. Initially, counts were conducted in December–February, but starting from 2006 – in mid-January. The participants included S.N. Erokhov from 2003 to 2005, O.V. Belyalov in 2003 and 2004, F.F. Karpov in 2004 and 2006, A.V. Kovalenko from 2005 to 2014 (Kovalenko, 2015), S.A. Kravchenko in 2005 and 2006, B.M. Gubin from 2016 to 2018 (Gubin, 2020), and the author together with A.Zh. Abayev and M.A. Yaganin in 2014, 2020–2022.